Ocean Warming Leads to Increases in Aerobic Demand and Changes to Gene Expression in the Pinfish (Lagodon rhomboides) - Eaton, Katherine M.; Hallaj, Adam; Stoeckel, James A.; Bernal, Moisés A. (Frontiers in Ecology and Evolution, 2022)
Anthropogenic climate change is causing increases in the frequency, intensity, and duration of marine heatwaves (MHWs). These short-term warming events can last for days to weeks and can produce severe disruptions in marine ecosystems, as many aquatic species are poikilotherms that depend on the conditions of the environment for physiological processes. It is crucial to investigate the effects of these thermal fluctuations on species that play a disproportionate ecological role in marine ecosystems, such as the pinfish (Lagodon rhomboides) in the Gulf of Mexico and western Atlantic. In this study, we exposed pinfish to a simulated MHW in aquaria and examined the impacts of acute warming on two life stages (juvenile and adult), measuring oxygen consumption and gene expression in two relevant tissue types (liver and muscle). We saw significant increases in routine metabolic rate with increasing temperature in both juveniles (24.58 mgO2/kg/h increase per 1°C of warming) and adults (10.01 mgO2/kg/h increase per 1°C of warming). These results indicate that exposure to increased temperatures was more metabolically costly for juveniles than for adults, on a mass-specific basis. This was also observed in the molecular analyses, where the largest number of differentially expressed genes were observed in the juvenile pinfish. The analyses of gene expression suggest warming produces changes to immune function, cell proliferation, muscle contraction, nervous system function, and oxygen transport. These results indicate that this ecologically relevant species will be significantly impacted by projected increases in frequency and magnitude of MHWs, particularly in the juvenile stage.